1998
DOI: 10.1046/j.1365-2346.1998.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of oropharyngeal Mallampati classification in predicting difficult laryngoscopy among obese patients

Abstract: The prediction of difficult intubation in obese patients was investigated by co-estimating the degree of visibility of oropharyngeal structures in conjunction with the respective body mass index. Data were collected prospectively in a series of 1833 consecutive adult patients. Body mass index (BMI) in kg m-2 was used as a measure of obesity (morbid: > 40, moderate: 30-40, no obesity: < 30). The oropharyngeal class findings were assessed using the original methodology as well as by a modification requiring the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
2
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 29 publications
4
46
2
2
Order By: Relevance
“…A large prospective study of 1,833 patients identified obesity is a factor predisposing difficult intubation. 12 The mean BMI of our OSAS patients was 27.9 ± 2.9, which would place our patients in their non-obese category.…”
Section: Discussionmentioning
confidence: 87%
“…A large prospective study of 1,833 patients identified obesity is a factor predisposing difficult intubation. 12 The mean BMI of our OSAS patients was 27.9 ± 2.9, which would place our patients in their non-obese category.…”
Section: Discussionmentioning
confidence: 87%
“…Two patients in CG had their trachea intubated at the third attempt with the gum elastic bougie and external laryngeal pressure applied to facilitate the laryngoscopic view. D Di is sc cu us ss si io on n Obesity has been found to be a risk factor for difficult intubation, 4,12 yet, Meyer 13 and Bond 5 failed to demonstrate a higher occurrence of difficult intubation in morbidly obese patients. Meyer 13 had shown that intubation difficulty in 400 morbidly obese patients was similar to that of non-obese patients.…”
Section: Discussionmentioning
confidence: 98%
“…4,5 The purpose of our study was to evaluate the impact of specific factors in predicting a DL in morbidly obese patients undergoing elective surgery.…”
Section: Résultats : Les Patients Du Ge éTaient Plus Jeunes (P < 000mentioning
confidence: 99%
“…Thus, a body mass index (BMI) Ͼ26 kg/m 2 results in a 3-fold increase in difficult ventilation via a mask (1) and in a 10-fold increased incidence of difficult endotracheal intubation (2,3). Inability to maintain a patent airway can be problematic in the obese, because lung and chest mechanical properties are markedly impaired in sedated, paralyzed obese patients (4).…”
Section: Anesth Analg 2003;96:1510 -5)mentioning
confidence: 99%
“…Preoperative prediction of potential difficulty with airway management by using individual tests, such as a Mallampati score, seems to have a lesser value in obese patients as compared with lean patients (2). Consequently, anesthesia of morbidly obese patients remains at frequent, but not foreseeable, risk of difficult mask ventilation or tracheal intubation.…”
Section: Anesth Analg 2003;96:1510 -5)mentioning
confidence: 99%